The Auditory Gaze : The Role of Knowledge Inclusivity in Hearing Audience Reception of Sign Language Interpreters at Indonesia Music Festivals - Fadhila, Rizka; Suharto, Bambang (Politeknik Pariwisata NHI Bandung, 2025)
This study aims to explore the role of knowledge regarding inclusivity on the perception of hearing audiences towards the use of Sign Language Interpreters (SLIs) at Indonesian music festivals. The research background stems from the high enthusiasm of Indonesian society for music concerts, as indicated by the 2024 Populix survey. Despite music being considered a universal language, accessibility for the Deaf community remains a significant issue. The use of SLIs at music concerts is a transformative step to bridge this gap, but its effectiveness depends on the perception and acceptance of hearing audiences. Methodology This study employs a quantitative design with a survey method, involving at least 100 hearing audience respondents who have attended music festivals in Indonesia. Purposive and snowball sampling techniques are used to reach the respondents. An online questionnaire with a Likert scale is used to measure inclusivity knowledge and perceptions of SLIs. The results of this study are expected to contribute to the understanding of how to enhance inclusivity at music festivals, highlighting the importance of knowledge and perception as key factors.